Menumbuhkan Kesadaran Orang Tua dalam Deteksi dan Intervensi Stunting Anak Sejak Dini - Inten Risna; Haerul Mustofa; Ichsan Ahmad Prasetyo; Uktafiya Nurhayati; Siti Marina; Ade Ifan Mujayanro; Dea Azhari; Albert Aderama; Fani Fardiani; Moch. Fikries Najmil Hak; Nur Yulia Prastiwi; Rafli Maulana; Septa Fauzi; Indah Fitriani; Ridwan Ridwan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Stunting is a chronic nutritional problem in children that occurs since in the womb and will have an impact on the child's growth and development in the future. The purpose of this community service activity is to raise public awareness and knowledge in detecting and intervening stunting in children as early as possible. The method used is the delivery of information related to stunting and demonstration of early detection of stunting. The targets of this community service activity are pregnant mothers and mothers who have toddlers in Tembong Village, Carita. The results showed a significant change between before and after participating in the counseling program, namely increasing knowledge and building commitment in mothers to continuously monitor the nutritional status and growth of toddlers at Posyandu.